Myocardin regulates expression of contractile genes in smooth muscle cells and is required for closure of the ductus arteriosus in mice - Huang, Jianhe (American Society for Clinical Investigation, 2008)
Myocardin (Myocd) is a potent transcriptional coactivator that has been implicated in cardiovascular development and adaptation of the cardiovascular system to hemodynamic stress. To determine the function of myocardin in the developing cardiovascular system, Myocd(F/F)/Wnt1-Cre(+) and Myocd(F/F)/Pax3-Cre(+) mice were generated in which the myocardin gene was selectively ablated in neural crest–derived SMCs populating the cardiac outflow tract and great arteries. Both Myocd(F/F)/Wnt1-Cre(+) and Myocd(F/F)/Pax3-Cre(+) mutant mice survived to birth, but died prior to postnatal day 3 from patent ductus arteriosus (PDA). Neural crest–derived SMCs populating the ductus arteriosus (DA) and great arteries exhibited a cell autonomous block in expression of myocardin-regulated genes encoding SMC-restricted contractile proteins. Moreover, Myocd-deficient vascular SMCs populating the DA exhibited ultrastructural features generally associated with the SMC synthetic, rather than contractile, phenotype. Consistent with these findings, ablation of the Myocd gene in primary aortic SMCs harvested from Myocd conditional mutant mice caused a dramatic decrease in SMC contractile protein expression. Taken together, these data demonstrate that myocardin regulates expression of genes required for the contractile phenotype in neural crest–derived SMCs and provide new insights into the molecular and genetic programs that may underlie PDA.